Design and analysis of dual band integrated hexagonal shaped microstrip UWB antenna - Alaa Farhood; Maham Kamil Naji; Suhad Hasan Rhaif Hasan Rhaif; Adnan Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, we proposed a hexagonal shaped microstrip ultra-wideband (UWB) antenna integrated with dual band applications. The antenna design consists of a hexagonal shape patch with two folded Capacitive Loaded Line Resonators (CLLRs) on the left edge of the patch antenna. This hexagonal structure is used to implement UWB applications (3.1-10.6 GHz). A rectangular ground, and two CLLR are also used on the bottom of antenna to obtain the extra dual resonant frequency at 2.4 GHz and 9.1 GHz for Bluetooth and radar applications respectively. The proposed design is implemented using FR4 epoxy substrate. The relative permittivity of the substrate is 4.4. The overall size of designing antenna is 26 × 30 mm2 with 1.6 mm as thickness and fed by standard feed line of 50 Ω microstrip. The results obtained from the simulation indicate that the designed antenna attains a good bandwidth from 1.1 GHz – 10.69 GHz with VSWR < 2 and return loss < -10 dB. The proposed geometry is simulated  by using the Ansoft HFSS simulator working on the principle of FEM and results are also analyzed.